Comparison of PAS and GMS Conventional Staining with Modification (PAS-Tartrazine And GMS-Phloxine Tartrazine) on Aspergillus and Coblastomycosis Fungi in Tissues: Perbandingan Pewarnaan Konvensional PAS dan GMS dengan Modifikasi (PAS-Tartrazine dan GMS-Phloxine Tartrazine) pada jamur Aspergillus and Coblastomycosis dalam Jaringan - Salma Nafisha; Miftahul Mushlih (Universitas Muhammadiyah Sidoarjo, 2026)
Fungal infections may occur in the lungs due to Aspergillus infection or in subcutaneous tissues as a result of chromoblastomycosis. Histopathological staining methods commonly used for fungal detection include Periodic Acid–Schiff (PAS) and Gomori's Methenamine Silver (GMS). This study aimed to compare the staining quality of conventional PAS and GMS methods with their modified counterparts, PAS-Tartrazine (PAS-T) and GMS-Phloxine Tartrazine (GMS-PT), in tissues infected with Aspergillus and chromoblastomycosis. This study employed a descriptive exploratory design and was conducted at Sudarma Medical Laboratory, Surabaya, in May 2024. The study samples consisted of paraffin-embedded tissue blocks stained using PAS, GMS, PAS-T, and GMS-PT methods. A total of six samples were examined, with each sample processed in duplicate. Staining quality was evaluated using a four-point scoring system (scores 1–4) based on the clarity of fungal structures, cell nuclei, and cytoplasm. The results were statistically analyzed using the Mann–Whitney test. The comparison between PAS and PAS-Tartrazine staining demonstrated significant differences (p < 0.05) in the visualization of fungal structures and cell nuclei. Likewise, comparison between GMS and GMS-Phloxine Tartrazine staining revealed significant differences (p < 0.05) in the visualization of cell nuclei and cytoplasm. PAS-Tartrazine staining provided clearer visualization of fungal structures than conventional PAS staining, whereas both GMS and GMS-Phloxine Tartrazine produced equally clear visualization of fungal structures.